Immunosensors in Early Cancer Diagnostics: From Individual to Multiple Biomarker Assays - Korecká, Lucie; Vytřas, Karel; Bílková, Zuzana (My University, 2018)
Cancer is a widespread disease characterized by high mortality. To improve the survival rate or facilitate effective therapy, accurate and reliable diagnosis at an early stage is needed. For this reason, there is a continuous push to develop sensitive methods which can be used in cancer diagnosis. Current diagnosis relies on the quantification of cancer biomarkers defined as molecules that are measurable in body fluids or tissues and indicate a change in physiological processes with subsequent pathological manifestations. This contribution reviews recent developments in the area of electrochemical immunosensors applicable for the detection of cancer biomarkers that occur in a wide concentration range including extremely low levels, which are typical for the early stage of the disease. A summary of various antibody labels used for biomarker analysis and combined with electrochemical detection is presented. The potential of multiple biomarker analysis, with its indisputable clinical impact for accurate diagnosis, is also highlighted.
Imunosenzory v časné diagnostice nádorů: Od individuální k multiplex analýze
Keywords: Cancer; diagnosis; biomarker; electrochemical detection; immunosensors; multiplex assay; Diagnostika nádorových biomarkerů; elektrochemická detekce; imunosenzory; multiplex analýza